(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Through the years, pedagogical research, the discovery of different learning styles, and technological improvements have all contributed to a substantial evolution in the teaching of English. Innovative teaching strategies are essential in today’s changing educational environment to keep students interested and help them acquire language effectively. This article examines some of the most cutting-edge approaches for teaching English, demonstrating how they can improve student and teacher empowerment and learning outcomes.